2011
DOI: 10.1186/1747-1028-6-7
|View full text |Cite|
|
Sign up to set email alerts
|

The loop-less tmCdc34 E2 mutant defective in polyubiquitination in vitro and in vivo supports yeast growth in a manner dependent on Ubp14 and Cka2

Abstract: BackgroundThe S73/S97/loop motif is a hallmark of the Cdc34 family of E2 ubiquitin-conjugating enzymes that together with the SCF E3 ubiquitin ligases promote degradation of proteins involved in cell cycle and growth regulation. The inability of the loop-less Δ12Cdc34 mutant to support growth was linked to its inability to catalyze polyubiquitination. However, the loop-less triple mutant (tm) Cdc34, which not only lacks the loop but also contains the S73K and S97D substitutions typical of the K73/D97/no loop m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Previous qualitative studies showed that deletion of the acidic loop of CDC34 led to increased ‘charging’ by E1 (Lass et al, 2011). To test whether this is a general feature of family three E2s, we deleted the acidic loop of Ubc15, hCDC34b, and hUBE2G2 and found that the thioester transfer activities of the resulting E2s were increased by 2–5 fold (Figures 2C and S2C).…”
Section: Resultsmentioning
confidence: 99%
“…Previous qualitative studies showed that deletion of the acidic loop of CDC34 led to increased ‘charging’ by E1 (Lass et al, 2011). To test whether this is a general feature of family three E2s, we deleted the acidic loop of Ubc15, hCDC34b, and hUBE2G2 and found that the thioester transfer activities of the resulting E2s were increased by 2–5 fold (Figures 2C and S2C).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we used here as a model system, the homolog of Cdc34 in yeast, Saccharomyces cerevisiae Cdc34 (ScCdc34 or Ubc3). Indeed, this enzyme has been extensively characterized by our and other works [13,23,[30][31][32][33] and an MD ensemble of conformations for ScCdc34 was already available [13,23]. ScCdc34 represents a valuable model since it shares a high sequence similarity with its human homolog (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We here focused on the Cdc34 acidic loop as a possible target of action for inhibitory molecules, which can constrain its position in the proximity of the catalytic cysteine, impairing Cdc34 activity. Indeed, the current data available on Cdc34 [13,23,[30][31][32][33] support that Cdc34 can populate both states in which the loop is in a 'closed' conformation and the catalytic cysteine not accessible for Ub-transfer by the E1 enzyme, and active 'open' state in which the loop is open or partially open and the catalytic cysteine in a solvent-exposed position that can thus be compatible with Ub-charging. Those active open states, which are likely to be present even in absence of phosphorylation, are suggested to be further promoted by phosphorylation of Cdc34 catalytic domain by a population-shift mechanism [13,23].…”
Section: Discussionmentioning
confidence: 99%
“…Gene deletions were used for the non-essential E2 enzymes Rad6, Ubc4, Ubc5, Ubc7, Ubc8, Pex4, Ubc11 and Ubc13. The polyubiquitylation-defective cdc34 tm mutant (Cocklin et al, 2011;Lass et al, 2011) was used for the essential E2 enzyme Cdc34 (which associates with SCF E3 ligases). Each of these mutations was combined with either ipl1-2 or glc7-127 and assayed for suppression of temperature sensitivity or a synthetic growth phenotype, respectively.…”
Section: E2 Ubiquitin-conjugating Enzymes Affect Ipl1-glc7 Functionmentioning
confidence: 99%